Assessment of risks relating to climate change within public organizations in the Oriental region of Morocco - EL HAJI , Hajar; AAMARA, Khadija (Revue du contrôle, de la comptabilité et de l’audit, 2024)
Obviously, the climate has changed and will continue to change during the 21st century. In the context of climate change, an organization whose areas of activity are sensitive to climate change may be more sensitive to climate risks in the future. There are several reasons why it makes sense to start thinking about and making progress on climate change adaptation. In this article, we propose to shed light on the concepts « Risk » and « Climate Risk » through a synthesis of the various theoretical and empirical works dealing with these notions. Additionally, a study was conducted among a sample of Moroccan public organizations to determine their perception of risk, as well as the specificities of their risk management approaches, and particularly the risks related to climate change. Indeed, the main objective of our work is to study the implementation of the second component of internal control, which is 'risk assessment,' within 50 public organizations in the Oriental region. We adopted a quantitative method and collected responses from 35 public organizations in the Oriental region, achieving a response rate of 70%.